Pengaruh Sanksi Pajak, Kesadaran Wajib Pajak, dan Tingkat Ekonomi terhadap Kepatuhan dalam Membayar Pajak Bumi dan Bangunan di Kecamatan Ngronggot Kabupaten Nganjuk - Erni Dwi Setyowati; Puji Astuti; Mar’atus Solikah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research is motivated by the low level of taxpayer compliance in paying Land and Building Tax (PBB) in Ngronggot District, Nganjuk Regency. This compliance problem is indicated by the high rate of delays and non-compliance in paying tax obligations, which is largely caused by weak enforcement of sanctions, low taxpayer awareness, and diverse economic conditions of the community. This study aims to analyze the influence of tax sanctions, taxpayer awareness, and economic level on compliance in paying PBB. The research method used is a quantitative approach with a survey technique, through the distribution of questionnaires to 100 taxpayer respondents selected using a simple random sampling technique. The data obtained were analyzed using multiple linear regression, accompanied by classical assumption tests such as normality tests, multicollinearity, heteroscedasticity, and hypothesis tests (t-test and F-test) to examine the influence of independent variables partially and simultaneously on the dependent variable. The results of the study indicate that partially, tax sanctions, taxpayer awareness, and economic level have a positive and significant influence on taxpayer compliance in paying PBB. Simultaneously, these three variables are also proven to have a significant influence on taxpayer compliance. These findings provide an important contribution to the formulation of regional fiscal policies, particularly regarding strategies for increasing regional tax revenue. Practical implications of this research include the need to increase the effectiveness of sanction enforcement, intensify tax outreach and education, and improve tax administration services to encourage public awareness and compliance. With the right strategies, it is hoped that taxpayer compliance will increase sustainably and contribute to optimizing regional revenue.